Spain: The Forward March of Podemos Halted?. Issue 4 (2nd October 2017) - Gillespie, Richard
Abstract: Impressive electoral performances by Podemos in its first European, municipal and regional elections have not been sustained in the Spanish general elections of December 2015 and June 2016. In the context of government austerity policies and systemic political crisis, this radical left populist party has certainly attracted much support among youth and disadvantaged sectors, and had a great impact on Spain's political life, yet so far Podemos has not managed to become the main alternative to the conservative Popular Party. Its alignment with the old United Left has proved unproductive and controversial. There have been tensions between the organizational centralism of the Podemos leadership and a desire for more decentralized expressions of radical politics in places such as Catalonia, as well as more generally from defenders of citizen politics or the original protest orientation of the party. For some currents of the left, Podemos has become too electorally oriented. Other critics point to a failure to reconcile left-wing objectives with the desire to capitalize on initial transversal appeal, extending beyond the traditional support base of the radical left. None the less, with Spain in a period of political stasis, there are still opportunities for Podemos to play a more influential role in the future, if it can address the challenges it faces without suffering schisms in the process.